Portuguese students' knowledge of antibiotics: a cross-sectional study of secondary school and university students in Braga - Baltazar Fátima; Yaphe John; Pinheiro Céline; Azevedo Maria (BMC, 2009)
Abstract Background Recent surveys show that the knowledge of the general public about the correct use of antibiotics is limited. This contributes to the problem of inappropriate antibiotic use, leading to a progressive loss of bacterial sensitivity to these drugs and the spreading of resistant strains of bacteria. Methods In this cross-sectional study, a questionnaire about antibiotic use was given to a sample of students in the 9th and 12th grades of secondary school and in the first year of university in the north of Portugal. Results 349 students returned completed questionnaires. Deficits were found in the students' knowledge of antibiotics and their correct use. Only 4% of 9th grade students were aware that antibiotics are used to treat bacteria only, while 14% of 12th grade students and 29% of first-year university students were aware of this. Fewer students were aware that antibiotics are used to treat tuberculosis. There were deficiencies in the knowledge of timing and duration of therapy. However close to 70% of these students are aware that inappropriate use of antibiotics can contribute to resistance to these drugs. Conclusion This study has observed a lack of general knowledge on correct antibiotic use in Portugal, as has been found in other countries. Since this may be due to a lack of formal education on this subject, we believe that a teaching unit on infectious diseases should be included in the 9th and 12th grades, in all curricular areas, with emphasis on bacterial and viral pathogens and correct antibiotic use. In addition, education on the correct use of medications may need to begin at much earlier ages.